Human-induced water loss potentially threatens sustainable development of sandy regions in China - Runa A; Xinliang Pan; Liudi Zhu; Kelvin T. F. Chan; Zhangcai Qin; Enliang Guo; Yuhai Bao; Song Qing; Tingwei Cui (Communications Earth & Environment)
Abstract Water is indispensable for sustainable socioeconomic development, especially in China’s sandy regions. Despite existing studies in sandy regions, the drivers of changes in total water storage and their potential impacts remain inadequately understood. Here we found a 55.97 billion m³ net loss in total water storage from 2002 to 2023 by integrating multiple datasets. Water loss was primarily attributed to increased farmland irrigation (49.56 billion m³) and ecological restoration (37.04 billion m³). In the coming 40 years, water supply capacity will decrease by up to 6.54% and 19.07% under low and high emission scenarios, respectively, requiring reductions in human water consumption of 60% to 135%. This depletion potentially threatens both regional sustainability and national ecological security. This study calls for urgent scientific regulations on water resources, including strict control of local consumption and enhancement of supply capacity.